Recent Developments in Computational Collective Intelligence - Badica, Amelia; Trawinski, Bogdan; Nguyen, Ngoc Thanh; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
The book consists of 19 extended and revised chapters based on original works presented during a poster session organized within the 5th International Conference on Computational Collective Intelligence that was held between 11 and 13 of September 2013 in Craiova, Romania. The book is divided into three parts. The first part is titled (3z(BAgents and Multi-Agent Systems(3y (Band consists of 8 chapters that concentrate on many problems related to agent and multi-agent systems, including: formal models, agent autonomy, emergent properties, agent programming, agent-based simulation and planning. The second part of the book is titled (3z(BIntelligent Computational Methods(3y (Band consists of 6 chapters. The authors present applications of various intelligent computational methods like neural networks, mathematical optimization and multistage decision processes in areas like cooperation, character recognition, wireless networks, transport, and metal structures. The third part of the book is titled (3z(BLanguage and Knowledge Processing Systems(3y(B, and consists of 5 papers devoted to processing methods for knowledge and language information in various applications, including: language identification, corpus comparison, opinion classification, group decision making, and rule bases.s
Agents and Multi-Agent Systems -- Intelligent Computational Methods -- Language and Knowledge Processing Systems.
Keywords: Engineering; Artificial intelligence; Engineering; Computational Intelligence; Artificial Intelligence (incl. Robotics).